Bioactive, degradable and multi-functional three-dimensional membranous scaffolds of bioglass and alginate composites for tissue regenerative applications. (23rd June 2020) - Bargavi, P.; Ramya, R.; Chitra, S.; Vijayakumari, S.; Riju Chandran, R.; Durgalakshmi, D.; Rajashree, P.; Balakumar, S.
Abstract : Multifunctional bioactive hydrogel ECM like membrane for 3D dynamic tissue/disease modelling. Abstract : With a worldwide increase in the aged populace and associated geriatric diseases, there is an enormous need for the regeneration of degenerated organ systems. For this purpose, bioactive glass particulate (nBG) integrated alginate (Alg) composite membrane scaffolds were fabricated by a sol–gel assisted freeze-drying method and validated for their multifunctional utility in regenerative medicine. The presence of the combeite highly crystalline structure of nBG and Alg amorphous broad peaks were confirmed. Repetitive peaks from acids along with stretching confirmed the chemical interactions of the composites. Swelling ability, porosity, and in vitro degradation and biomineralization were analysed for up to 7 days. The results indicated that reduced swelling and degradation enhanced apatite formation. Hemocompatibility and the hemostatic properties on scaffolds were also systematically investigated. Additionally, significant cyto-compatibility and proliferation were noted in a culture with KB3-1. Further 3-D co-cultures with HDF cells and KB3-1 cells exhibited spheroid formation on Alg, nBG/Alg and nBG-Zr/Alg with profound dynamism required to establish organoids of interest. Thus, the results indicate that these 3D hydrogel membranes could offer infinite possibilities in the field of regenerative medicine, notably as an extracellular matrix (ECM) supporting the regeneration of bone, intra-vascularization, and neo-tissue formation, such as cartilage and ligaments.